Unhealthy Assimilation : Do Immigrants Converge to American Weights? - Heather Antecol; Kelly Bedard (Claremont McKenna College, Department of Economics, 2004)
It is well documented that immigrants are in better health upon arrival in the United States than their American counterparts, but that this health advantage erodes over time. We study the potential determinants of this "healthy immigrant effect", with a particular focus on the tendency of immigrants to converge to unhealthy American weight levels. Using data from the National Health Interview Survey, we find that the average female and male immigrants enter the U.S. approximately two and five percentage points lighter than native-born white men and women, respectively. And, consistent with the declining health status of immigrants the longer they remain in the United States, we also find that female immigrants completely converge to American weights within ten years of arrival and men close a third of the gap within fifteen years.
Keywords: 330; Migranten; Gesundheit; Schätzung; Vereinigte Staaten; Körpergewicht